Integrating Ros and Iot in a Virtual Laboratory for Control System Engineering - Urrea-Onate, E; Kern-Molina, J (Hindawi Limited, 2020)
This article presents the implementation of a learning environment for the teaching of control systems. This environment integrates physical equipment and simulation, monitoring, and control through a network. A software platform based on ROS (Robotic Operating System) grants access to the system through intranet and Internet, facilitating the integration of new test equipment. The environment developed can be used in didactic experiences both inside and outside the classroom, enhancing the learning of four main study topics: modeling, analysis, parameter estimation, and controller design. © 2020 Claudio Urrea and John Kern.